Andrographis paniculate Leaves Extract Impacts the Immune Response of Salmonella-Infected Mice - Purnaning Dhian Isnaeni; muhammad amrullah Pagala; Muh. Rusdin; Takdir Saili; Deki Zulkarnain; Andi Murlina Tasse (Pascasarjana Universitas Sulawesi Tenggara, 2023)
Andrographis paniculate (AP) is one of the traditional herbs of Indonesia that contains andrographolide and has immunomodulator, antibacterial, and antiviral activities. Leucocyte is part of the specific immune system that protects the organism from infection by pathogens, and its response can be affected by immunomodulators such as andrographolide. This study used 60 mice divided into 5 treatment groups of different AP extract doses (control negative, control positive, KS1: 200 mg/kg BW, KS2: 300 mg/kg BW, KS3: 400 mg/kg BW) and was done by completely randomized design. AP extract was given to treatment groups for 21 days. On day 22, mice were orally challenged by Salmonella typhi infection, and blood samples were collected on day 24. Results of this study showed a decreasing leucocyte count in mice treated with AP extract and challenged with S. typhi compared to control positive (untreated and infected group). The results also showed a shift in differential leucocyte percentage in treated groups closer to the normal number in the control negative (untreated and uninfected) group. AP extract at 400 mg/kg BW can be used as an immunomodulator to improve mice's immune response to Salmonella typhi infection.